Location, Orientation and Buoyance Effects of Radical Probes as Studied by Epr - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C (Springer International Publishing, 2022)
hen measuring antioxidant activities in micelles and emulsions, the location of the antioxidant or of the probe has long been recognized as an important issue. The present chapter represents one step further in these studies, by drawing attention to the importance of the proximity between the interacting centers of a probe/antioxidant pair, even when the two species are located in the same or in similar environments. The use of 4-alkanoyloxy-1, 1, 6, 6-tetramethylpyperidineoxyl (TEMPO) radicals as probes for AOs in micellar systems or emulsions, reveals cut-off patterns that suggest a novel interpretation of the polar paradox, based on the orientation of the probe and/or AO in these systems. Changes in orientation in a micro-heterogeneous medium are associated with structural features of these molecules, and with their amphiphobic character. These molecules are characterized by possessing two end-groups of variable lipophilicity. In a heterogeneous interface, a competition is established between these groups for the hydrophobic core of a micelle or emulsion droplet, leading to distinct orientations and degrees of insertion into the lipophilic core. The whole process is adequately described by a schematic depiction, the “diving-swan” analogy. Examples from the literature of this process and of cut-off patterns of behavior for various AOs in micro-heterogeneous systems are presented and discussed. They give support to this approach, originally developed from observations with the behavior of the 4-substituted TEMPO derivatives as probes in these systems. As the polar paradox is a rather general phenomenon, encountered not only in the assessment of antioxidant activities in food extracts but also in a larger variety of biological systems, the present approach can find interesting applications in the future, in the analysis of this paradox in biological systems. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.